2018
DOI: 10.3389/fped.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models to Study Podocyte Biology: Stock-Taking the Toolbox of Glomerular Research

Abstract: Diseases affecting the glomeruli of the kidney, the renal filtration units, are a leading cause of chronic kidney disease and end-stage renal failure. Despite recent advances in the understanding of glomerular biology, treatment of these disorders has remained extraordinarily challenging in many cases. The use of experimental models has proven invaluable to study renal, and in particular, glomerular biology and disease. Over the past 15 years, studies identified different and very distinct pathogenic mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…For decades, murine and human 2D conditionally immortalized podocytes (ciPOD) have been used to unravel NS pathophysiology. Although these models have expanded our knowledge regarding podocytopathies in NS, we and others showed that in vitro 2D conditionally immortalized podocyte models do not meet in vivo podocyte characteristics (Hagmann and Brinkkoetter, 2018; Hale et al, 2018; Rinschen et al, 2018; van den Broek et al, 2021). Here, we showed that kidney organoids are a promising tool to study both congenital and idiopathic nephrotic syndrome since organoid podocytes express essential proteins, with a morphology closely resembling in vivo podocytes, and respond similarly to injury triggers.…”
Section: Discussionmentioning
confidence: 97%
“…For decades, murine and human 2D conditionally immortalized podocytes (ciPOD) have been used to unravel NS pathophysiology. Although these models have expanded our knowledge regarding podocytopathies in NS, we and others showed that in vitro 2D conditionally immortalized podocyte models do not meet in vivo podocyte characteristics (Hagmann and Brinkkoetter, 2018; Hale et al, 2018; Rinschen et al, 2018; van den Broek et al, 2021). Here, we showed that kidney organoids are a promising tool to study both congenital and idiopathic nephrotic syndrome since organoid podocytes express essential proteins, with a morphology closely resembling in vivo podocytes, and respond similarly to injury triggers.…”
Section: Discussionmentioning
confidence: 97%
“…The protein products of these canonical podocyte genes are essential for the proper podocyte function. In cell culture, human and mouse podocytes also lose expression of NPHS1 and NPHS2, 23,24 and this downregulation or loss in FSGS urinary podocytes could be due to podocyte injury or dedifferentiation. EMT is important in cancer biology, in which it contributes to increased mobility of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The podocytes in culture encounter neither the conventional mechanical stretch nor the flow of primary urine filtrate. Thus, it is not surprising that they do lack SDs in between neighboring cells (51) and also express only a limited amount of specific marker proteins such as nephrin, podocin, or transient receptor potential cation channel 6 (TRPC6) (52). In order to test if these conditionally immortalized podocytes can tolerate the physiological intraglomerular conditions, several mechanical and fluid shear stress models were generated to imitate the in vivo conditions (53)(54)(55).…”
Section: Immortalized Podocytes -Constitutive and Conditionalmentioning
confidence: 99%